2021
DOI: 10.21608/bmfj.2021.100688.1503
|View full text |Cite
|
Sign up to set email alerts
|

Ectasia risk score system and practical subjective scoring system in screening of keratorefractive surgery candidates

Abstract: Background: Corneal ectasia is a sight-threatening complication of excimer laser refractive surgery with progressive thinning of the cornea, estimated between 0.04% and 0.6%. Aim of the work: Evaluate the sensitivity, specificity, and accuracy of ectasia risk score system and the practical subjective scoring system (PS3) in screening keratorefractive surgery candidates. Patients and methods: This retrospective study was included 226 eyes at Ebsar Eye Center, Benha, Egypt, subjects divided into 5 groups based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…A recent study by Elhusseiny et al showed that the ERSS was sensitive, specific, and accurate in screening keratorefractive surgery candidates. 30 Similarly, our study results detected a preoperative ERSS higher than three in 62.5% of eyes that developed post-LASIK ectasia. than eight could be candidates for laser surface ablation according to the value of their refractive error and the corneal thickness.…”
Section: Dovepresssupporting
confidence: 80%
“…A recent study by Elhusseiny et al showed that the ERSS was sensitive, specific, and accurate in screening keratorefractive surgery candidates. 30 Similarly, our study results detected a preoperative ERSS higher than three in 62.5% of eyes that developed post-LASIK ectasia. than eight could be candidates for laser surface ablation according to the value of their refractive error and the corneal thickness.…”
Section: Dovepresssupporting
confidence: 80%